The good earth - Bertozzi, Nick (Simon & Schuster, 2017)
In The Good Earth, Pearl S. Buck paints an indelible portrait of China in the 1920s, when the last emperor reigned and the vast political and social upheavals of the twentieth century were but distant rumblings. This moving story of the honest farmer WangLung and his selfless wife O-Lan is must reading to fully appreciate the sweeping changes that have occurred in the lives of the Chinese people during the last century. Though more than eighty years have passed since this remarkable novel won the Pulitzer Prize, it has retained its popularity and become one of the great modern classics in American literature.